ASSESSMENT OF PSYCHOTECHNICAL PARAMETERS OF VEHICLE DRIVERS ON ROUNDABOUT HITACHI TAGA, JAPAN - Elżbieta MACIOSZEK; Nan KANG (Scientific Journal of Silesian University of Technology. Series Transport)
The assessment of psychotechnical parameters (that is, critical gaps and follow-up times) of vehicle drivers at roundabout Hitachi Taga, Ibaraki Prefecture in Japan was presented in this paper. The basis for this assessment were empirical data from measurements in the field, made in two different years. The first field measurement took place two years after the construction of the roundabout in 2014, and the second one in 2019. The results comparison of 2014 and 2019 was aimed at assessing possible changes in the psychotechnical parameters in time. This assessment was carried out as one of the element of the project titled “Analysis of the applicability of the author's method of roundabouts entry capacity calculation developed for the conditions prevailing in Poland to the conditions prevailing at roundabouts in Tokyo (Japan) and in the Tokyo surroundings”, financed by the Polish National Agency for Academic Exchange.